Learner Characteristics based on Generational Differences - Thaariq, Zahid Zufar At (Jurnal Pendidikan Humaniora, 2023)
The development of an era that has always been mediated by technology has influenced the generational differences that adapt in each time. The context of learning that is carried out tends to transform according to the differences in generations. This study seeks to review the characteristics of learners based on existing generational differences. The approach used is in the form of a traditional literature review where the author reveals a discussion that is in accordance with the literature that the author finds. The literature sought focuses on generational differences that will then be attributed to the characteristics of learners. The result of this review is in the form of differences in the characteristics of learners based on the generation of birth. The greatest generation (GI) focuses on initiatives in learning. The veteran (silent) generation focuses on standardizing learning. Baby boomers are focusing on learning independence. Generation X focuses on learning balance. Generation Y (millennials) focus on controlling learning independently. Generation Z focuses on abstract learning constructions. The alpha generation focuses on creativity. The last (likely) beta generation focuses on complex learning processes with the help of surrounding artificial intelligence. This review is expected to contribute through exposure that can be an alternative reference for the world of education.